W-Power N-Binormal Operator on Hilbert Space - Mohammed , Dr. Alaa Hussein (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In this paper we present a new class of operators on Hilbert space called w-power n-binormal operator. We study this operator and give some properties of it.